Analysis of caesarean section rates in Malta using the Robson ten-group classification system - Sant Fournier, Kristina; Gatt, Miriam; Calleja, Neville (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Caesarean section (CS) rates continue to rise globally. In Malta, the rate of caesarean deliveries has increased by eight percentage points over the past two decades. The World Health Organization recommends the use of the Robson classification as a global standard for monitoring and auditing CS. This study aimed to examine CS rates in the Maltese Islands across two time periods using the Robson classification. Methods: A retrospective, registry-based study was conducted covering all deliveries between 2009-2013 and 2019-2023. Women undergoing childbirth in Malta and Gozo were allocated to one of the 10 Robson groups. Changes in overall CS rates and contributions by Robson group between the two periods were analysed using significance tests. Indications for CS were analysed for 2019-2023. Results: A total of 42,585 deliveries were analysed across both periods. Despite more advanced maternal age and a higher proportion of non-Maltese mothers over the time periods, the CS rate remained stable (31.9% in 2009-2013; 32.6% in 2019-2023). Contributions to the overall CS rate of Robson groups 5 (previous CS), 6 and 7 (breech) increased significantly, whilst contributions of groups 1 (nullipara, spontaneous labour), 2 (nullipara, induction/pre-labour CS), 8 (multiple pregnancies), and 10 (preterm) decreased significantly between study periods. The top contributors remained Robson groups 5 and 2, followed by 1. Conclusions: The Robson classification allows identification of the obstetric populations driving CS use. Our study findings provide a starting point for auditing of obstetric practices with a view to reducing CS rates.